Mensuração e distribuição espacial da eficiência dos gastos públicos em saúde nos municípios do estado do Paraná - Franceschina , Simone (2019)
Evaluating the quality of public spending, by verifying their efficiency in the provision of public services, it is becoming increasingly important in a scenario of increasing population needs, and scarcity of public resources. In this context, the purpose of this study was to analyze the efficiency of public health expenditures in relation to the provision of public health services and in the improvement of performance indicators in this segment, in the municipalities of the Paraná, from 2013 to 2015. In order to meet the objective, was used first the Data Envelopment Analysis (DEA) methodology, composed of eight study variables (four inputs and four products), product-oriented and with constant return of scale (CCR), was used for the first stage of the study, in the verification of the indices of technical efficiency. Then, the Exploratory Analysis of Spatial Data (AEDE) method will be used to verify the spatial patterns of location of the obtained efficiency scores. Data were secondary, from 330 municipalities of Paraná included in the sample, from the database of the Department of Informatics of the Unified Health System (DATASUS) and the Paranaense Institute for Economic and Social Development (IPARDES)The results of the first stage of the analysis showed that 51 (15.45%) of the 330 municipalities analyzed were efficient in the analyzed period. Of the remainder, 14 municipalities (4.24%) were identified with weak inefficiency, 45 (13.64%) with moderate inefficiency and a large part of the sample, 220 (66.67%) municipalities were highly inefficient. It was also pointed out that the municipalities with the highest level of efficiency are generally small (less than 10,000 inhabitants), and performed expenses lower than the general average. The results of the second stage of the analysis, obtained through the AEDE, indicate the existence of positive spatial autocorrelation in the data, that is, there is similarity between the values of the efficiency / inefficiency scores of the municipalities and their spatial location. Thus, the municipalities with above-average rates are surrounded by municipalities that also have values above average, and municipalities with below-average scores are surrounded by municipalities in the same situation. The LISA cluster maps indicated the existence of two significant Alto-Alto clusters, located in the pioneer North mesoregion and Northwest Paranaense. In addition to four significant low-low clusters, which encompass the Western Paranaense, Northweste Paranaense and Metropolitan Regions of Curitiba.